Descentralización fiscal, calidad de gestión de gobierno y disparidad interregional en el Perú, entre los años 2000 y 2017 - Arévalo Tantahuatay, Maritza (Universidad Nacional Agraria de la Selva, 2021)
The current investigation was carried out in Peru. The hypothesis that the research has answered is fiscal decentralization and the quality of government management influence interregional disparity in Peru between 2000 and 2017. Data collected from the Central Reserve Bank of Peru, from the National Registry of Municipalities- INEI and the National Agricultural Survey-INEI have contributed in estimating the dynamic panel data model of Arellano-Bond, the results obtained were a 100% increase in the tax revenues of the regions or in the total expenditure on salaries to public officials or increasing the Gross Domestic Product by 1% contribute to increasing the regional disparity in the 24 regions by 13% or decreasing by 9% or 8.12%.